DIAFILTRATION OF ULTRAFILTRATION RETENTATE OF WHEY FROM WHITE BRINED CHEESE - Maria DUSHKOVA (Journal of Central European Agriculture, 2012)
Whey diafiltration was carried out with a UF25-PAN polyacrylnitrilic membrane with 25 kDa molecular weight cut-off at volume reduction factors (VRF) VRF=2, VRF=4, VRF=6, VRF=8, VRF=10. The values of the principal components dry matter, protein, lactose and mineral substances in the retentates and permeate obtained were established. The relative shares of protein, lactose and mineral substances in the dry matter, the concentration factor (CF) values for dry matter, protein, lactose and mineral substances, and the protein retention factor (RF) were determined. Linear models were created for the CF of each investigated component according to the VRF, and a logarithmic model was developed for the protein RF according to the VRF. The results obtained demonstrated the efficiency of diafiltration for deep treatment aimed at a further elimination of lactose and mineral substances and subsequent utilization of the diafiltration concentrates low in lactose and mineral substances as a liquid supplement in the manufacture of extruded cereal products.